1995
DOI: 10.1037/0022-0167.42.3.338
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the development of the working alliance using hierarchical linear modeling.

Abstract: The relation between the working alliance and therapeutic outcome was examined in 21 therapist-client dyads. This relation was analyzed in terms of the level of alliance at the third counseling session, midpoint of treatment, and last session with linear and curvilinear models of the temporal development of the working alliance. Analyses were conducted with hierarchical linear modeling. Results revealed a significant association between the linear growth function of therapist ratings of the working alliance an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
151
5
7

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(184 citation statements)
references
References 42 publications
(61 reference statements)
21
151
5
7
Order By: Relevance
“…This result is consistent with the psychotherapy literature, which shows that the working relationship between the therapist and the client increases with the number of therapy sessions (Kivlighan & Shaughnessy, 1995). The number of sessions also refers to the design of executive coaching.…”
Section: Variablessupporting
confidence: 81%
See 2 more Smart Citations
“…This result is consistent with the psychotherapy literature, which shows that the working relationship between the therapist and the client increases with the number of therapy sessions (Kivlighan & Shaughnessy, 1995). The number of sessions also refers to the design of executive coaching.…”
Section: Variablessupporting
confidence: 81%
“…Finally, in the psychotherapy literature development of the working alliance over a series of sessions has been examined in a number of studies (de Roten et al, 2004;Kivlighan & Shaughnessy, 1995, 2000. These studies have shown that, in general, the working alliance tends to adopt two patterns: either a progressive increase in quality over the series of sessions or development in a quadratic pattern characterized by the three phases of initial optimism, then frustration and negative reactions during the period of working on the issues of therapy, and finally a positive reaction based on more realistic perceptions than those present in the initial phase.…”
Section: The Coach-coachee Relationship In Executive Coachingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the previous longitudinal reciprocal research (e.g., (Falkenström et al, 2014) investigating the effect of the working alliance typically Reciprocal Model of Working Alliance and Therapeutic Outcome 7 adopted a single alliance rating at the third session. Such an approach fails to recognize the change of the working alliance over time (Kivlighan & Shaughnessy, 2000;Kivlighan & Shaughnessy, 1995;Stiles et al, 2004) and ignores the enhancement of the working alliance-outcome link over time (Flückiger, Del Re, Wampold, Symonds, & Horvath, 2012;Martin et al, 2000). An examination exploring the reciprocal effects of the fluid working alliance and the fluid therapeutic outcome across the therapy course is thus needed.…”
Section: Reciprocal Model Of Working Alliance and Therapeutic Outcomementioning
confidence: 99%
“…Apesar da falta de consenso entre os estudos da relação terapêutica no aconselhamento psicológico vocacional, esta foi apontada como responsável de 1% a 12% pelos seus resultados , reforçando a conclusão que os resultados do aconselhamento psicológico vocacional podem ser explicados pela qualidade da relação terapêutica (Gunderson, Najavits, Leonhard, Sullivan, & Sabo, 1997;Kivlighan & Shaughnessy, 1995).…”
Section: Aconselhamento Psicológico Vocacional E Pessoal: Fatores Comunsunclassified